Release angle for attaining maximum distance in the soccer throw-in - Linthorne, N. P.; Everett, D. J. (Sports Biomechanics, 2006)
We investigated the release angle that maximizes the distance attained in a long soccer throw-in. One male soccer player performed maximum-effort throws using release angles of between 10 and 60 degrees, and the throws were analyzed using two-dimensional videography. The player's optimum release angle was calculated by substituting mathematical expressions for the measured relationships between release speed, release height and release angle into the equations for the flight of a spherical projectile. We found that the musculoskeletal structure of the player's body had a strong influence on the optimum release angle. When using low release angles the player released the ball with a greater release speed and, because the range of a projectile is strongly dependent on the release speed, this bias toward low release angles reduced the optimum release angle to about 30 degrees. Calculations showed that the distance of a throw may be increased by a few metres by launching the ball with a fast backspin, but the ball must be launched at a slightly lower release angle.